Cooperation Between Counselingcourses Teachers Andteachers in Helping Students' Learning Activities - Sawal Mahaly; Emma Rumahlewang (International Journal of Education, Information Technology, and Others, 2021)
Based on observations, the impression that the cooperation between teachers with subject teachers BK has not run its full potential in other words are still low. It is feared to affect the learning activities of students, because teachers are that factors that can in helping students learn activities. This research aims to describe collaboration between BK teachers with subject teachers in helping students' learning activities. The research is a type of quantitative research, as for the design of this study using a descriptive approach, the descriptive approach to describe a systematic, faktual facts and specific populations or try to describe the phenomenon in detail what it is. The study population was all teachers in junior UNP Development Lab Padang, amounting to 38 people, with samples taken at sampling saturation. The instrument used was a questionnaire likert scala model. The percentage of data analysis techniques. The results of this study concluded that there cooperation between teachers BK subjects with teachers in helping students learning activities, with scores generally in the achievement of 76.52% of respondents in the medium category. Given the results of this research is expected, so that teachers and subject teachers BK to re-evaluate program activities to be carried out and trying to create a harmonious relationship within the task.